Morphometric Variations of Discophrya elongata (Ciliophora, Suctorea) Attached to Two Different Species of Aquatic True Bugs (Hemiptera, Prosorrhyncha, Nepomorpha) - Marino-Perez, R.; Mayen-Estrada, R.; Macip-Rios, R.; Dovgal, I.V. (Вестник зоологии, 2011)
Morphometric variation in Discophrya elongata living as epibionts of two species of aquatic true bugs, Corisella edulis and Notonecta unifasciata, collected from the same pond in Mexico are discussed. Factors that may be responsible for observed variability, especially hydrodynamic loads and long-term modifications, also are identified and discussed.